2017
DOI: 10.1007/s10072-017-3123-2
|View full text |Cite
|
Sign up to set email alerts
|

Rasagiline for dysexecutive symptoms during wearing-off in Parkinson’s disease: a pilot study

Abstract: Wearing-off refers to the predictable worsening of motor and sometimes non-motor symptoms of Parkinson's disease occurring at the end of levodopa dose that improves with the next drug dose. Here, we investigated the efficacy of rasagiline on executive functions at the end of levodopa dose in patients displaying symptoms of wearing-off. Rasagiline was well-tolerated and produced a significant improvement at the Frontal Assessment Battery, together with improvement of motor symptoms at the end of levodopa dose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Two single-center open-label prospective studies from the same group investigated the effects of MAO-BIs in PD patients with wearing-off 67 , 68 . The unique point of these studies was that cognitive assessments were performed 20 min before the second scheduled daily dose of levodopa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two single-center open-label prospective studies from the same group investigated the effects of MAO-BIs in PD patients with wearing-off 67 , 68 . The unique point of these studies was that cognitive assessments were performed 20 min before the second scheduled daily dose of levodopa.…”
Section: Resultsmentioning
confidence: 99%
“…Other NMS might improve through alleviation of non-motor fluctuations 91 . Open-label studies have suggested that executive dysfunctions related to non-motor fluctuations improved with MAO-BIs 67 , 68 . Future studies should investigate the effects of MAO-BIs specifically on NMS with or without fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, neurosurgical procedures and optimal pharmacological management have been shown ineffective in improving cognitive functions, even though MAO-B inhibitors may improve cognitive symptoms during wearing-off (6). DBS-related cognitive outcomes are heterogeneous (7).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, attention and inhibition of cognitive interference were significantly ameliorated by high-dose safinamide, suggesting increased modulatory performances of prefrontal cortical pathways. Findings on inhibitory control were opposite to those obtained with rasagiline, 40 and this may depend on safinamide glutamatergic inhibition.…”
Section: Introduction To Safinamidementioning
confidence: 69%